2014
DOI: 10.1097/tld.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Coverage of Indicators of Response to Intervention

Abstract: Purpose Agreement across methods for identifying students as inadequate responders or as learning disabled is often poor. We report (1) an empirical examination of final status (post-intervention benchmarks) and dual-discrepancy growth methods based on growth during the intervention and final status for assessing response to intervention; and (2) a statistical simulation of psychometric issues that may explain low agreement. Methods After a Tier 2 intervention, final status benchmark criteria were used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Here, it is important to recognize that assessments of achievement by norm-referenced tests and by a CBM may be used jointly to operationalize the low achievement and instructional response components of the triangle approach to definition. In Fletcher et al (2014), no single measure was reasonably accurate in identifying the pool of inadequate responders. However, the norm-referenced assessment of untimed word-reading accuracy and a CBM assessment of oral reading fluency concurred in identifying 90/104 of the pool of inadequate responders; the 14 not identified were all average achievers and likely false positives.…”
Section: Some Potential Solutionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Here, it is important to recognize that assessments of achievement by norm-referenced tests and by a CBM may be used jointly to operationalize the low achievement and instructional response components of the triangle approach to definition. In Fletcher et al (2014), no single measure was reasonably accurate in identifying the pool of inadequate responders. However, the norm-referenced assessment of untimed word-reading accuracy and a CBM assessment of oral reading fluency concurred in identifying 90/104 of the pool of inadequate responders; the 14 not identified were all average achievers and likely false positives.…”
Section: Some Potential Solutionsmentioning
confidence: 91%
“…However, a great deal of work remains to be done to show that assessments of growth add to the information provided by the end-point final status measure. In Fletcher et al (2014), adding the slope to the final status assessment likely added many adequate achievers to the pool of inadequate responders. Moreover, empirical studies of the value-added information of slopes have not shown that additional information is obtained.…”
Section: Some Potential Solutionsmentioning
confidence: 98%
See 1 more Smart Citation
“…All students who met the criteria of a composite standard score on the Test of Word Reading Efficiency (TOWRE) or a Basic Skills Cluster standard score on the Woodcock–Johnson III Tests of Achievement (WJ III; Woodcock, McGrew, & Mather, 2001) less than 93 (i.e., below the 30th percentile) were selected for participation ( n = 218). This benchmark has been validated against external criteria as an indicator of adequate response to reading intervention at the end of Grade 1 (Fletcher et al, 2014) and used in several previous studies (Mathes et al, 1995; Torgesen, 2000). These students were randomly assigned to receive supplemental small-group intervention using a GR approach (GR group; n = 74) or an explicit instruction approach (EX group; n = 73), or the typical reading instruction and intervention provided by their schools, with no researcher-provided intervention (TSI group; n = 71).…”
Section: Methodsmentioning
confidence: 99%
“…We expected that preschool RTI tier-level proportions in programs would be influenced by child factors such as poverty, the language spoken at home, and special needs status (e.g., Shanahan & Lonigan, 2008). We also expected proportions would be influenced by the measures selected for use and the constructs, content, and methods that they reflected (e.g., Fletcher, Stuebing, Miciak, & Denton, 2012). This information about proportions of children identified for greater instructional intensity is fundamental for programs seeking to address critical policy questions about feasibility and the resources, staff, time, and cost needed to implement RTI.…”
Section: Introductionmentioning
confidence: 98%